Jan Paweł II wobec przemocy, ze szczególnym uwzględnieniem treści encykliki Centesimus Annus - Debita, Magdalena (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The main purpose of this article is to present John Paul II’s views on the subject of violence, which the Polish Pope regarded as one of the threats to living in accordance with the commandments and norms of religion and Christian ethics. The author predominantly focuses on analyzing the Centesimus Annus encyclical issued in 1991. Both its title and content contain many references to Leo XIII’s encyclical Rerum Novarum, published precisely 100 years earlier. In his own teaching, John Paul II distinguishes moral and social aspects of violence. According to these papal reflections, violence has many sources and substrates that make it difficult for men to combat
Keywords: John Paul II (pope; 1920-2005); encyclical; Centesimus Annus; Papal teaching